Tethered Aminohydroxylation Reaction and Its Application to Total Synthesis - Donohoe, T; Callens, C; Lacy, A; Winter, C (2012)
This review highlights key aspects of the Tethered Aminohydroxylation from its discovery to its current incarnation, which employs N,O-acylated derivatives as reoxidants for osmium. The potential and generality of this reaction has been demonstrated by its application in the synthesis of several natural products. A review of the recently developed N-O reoxidants for the tethered aminohydroxylation (TA) reaction is presented. All aspects of the aminohydroxylation reactions that are facilitated are discussed, together with their application in total synthesis. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.